Technological change in economic models of environmental policy: A survey - Andreas Löschel (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper provides an overview of the treatment of technological change in economic models of environmental policy. Numerous economic modeling studies have confirmed the sensitivity of mid- and long-run climate change mitigation cost and benefit pro-jections to assumptions about technology costs. In general, technical progress is considered to be a non-economic, exogenous variable in global climate change modeling. However, there is overwhelming evidence that technological change is not an exogenous variable but to an important degree endogenous, induced by needs and pressures. Hence, some environment-economy models treat technological change as endogenous, responding to socio-economic variables. Three main elements in models of technological innovation are: (i) corporate investment in research and development, (ii) spillovers from R&D, and (iii) tech-nology learning, especially learning-by-doing. The incorporation of induced technological change in different types of environmental-economic models tends to reduce the costs of environmental policy, accelerates abatement and may lead to positive spillover and negative leakage.
Keywords: C50; C68; O30; Q25; 330; Climate policy; exogenous technological change; induced technological change; environment-economy models; Umweltökonomik; Klimaschutz; Technischer Fortschritt; Endogener technischer Fortschritt; Theorie